Revisions of Aboriginal Identity: Being or Becoming? - Polak, Iva (2005)
The paper focuses on the tensions between “representation” and “representativeness” and how Australian Aboriginal authors have been negotiating between the two. The inability to firmly define Aboriginal and Australian identity is not based on the concept of the self (identity) not given to consciousness, but rather on the self coming to consciousness in a society undergoing reconstruction. The place of (local) utterance/identity is positioned in the framework of frequently discussed Australian multiculturalism.
Projekt MZOS
ENG